A clinical study of NM441 - Tsubura, Eiro; Masuno, Tomiya (Japanese Journal of Chemotherapy, 1996)
NM441, a new quinolone antibiotic, was administered to 3 patients with respiratory tract infections (2 with chronic bronchitis and 1 with pulmonary emphysema + infection), and the clinical efficacy and safety of this drug were investigated. NM441 was administered at a dose of 100mg twice a day for 13-14days. The clinical response was good in 1 and poor in 2 of 3 cases. No side effects were observed, but mild elevation of S-GOT and S-GPT was observed in 1 patient.